The optical transmission studies of tin oxide thin film doped with flourine - 445636 Yussof Wahab; K. A. B. Ali; Premraj A/L Arumugam; Regional Confernce on Solid State and Science and Technology (21st : Kota Kinabalu, Sabah) (Skudai : Universiti Teknologi Malaysia, 2004)
40